Antitumor effects of Freeze-Dried Robusta Coffee (Coffea canephora) extracts on breast cancer cell lines - Nigra, Ayelén Denise (2021)
Coffee consumption is believed to have chemopreventive and chemotherapeutic effects and to contribute to preventing the development and progression of cancer. However, there is still controversy around these claims. As indicated in our previous works, diet can influence the risk of breast cancer. Intake of coffee is hypothesized to reduce this risk, but current scientific evidence is not conclusive. This work is aimed at studying the effects of Robusta coffee bean extract on cell viability, proliferation, and apoptosis of different human cancers, especially breast cancer cell lines. To this end, cell viability was evaluated by Alamar Blue in 2D and 3D models, the cell cycle by PI, apoptosis by annexin V, mitochondrial morphology, and functionality by mitoTracker, and colony formation capacity by the clonogenic assay. Green and dark coffee extract significantly reduced viability in human breast, colorectal, brain, and bone cancer cells. Coffee anticancer activity was clearly evidenced in MDA-MB-231 (ER-) and MCF-7 (ER+) breast cancer cells but not in the normal breast cell line. In addition, coffee extract induces an increase S phase and a decrease G2/M population in breast cancer cells, affected the mitochondrial morphology, and triggered apoptosis. MDA-MB-231 breast cancer cells lost their clonogenic capacity after treatment. The antitumor activity was demonstrated in both 2D and 3D culture cell models.